Guadua angustifolia como materia prima para mercados potenciales desde Colombia (2023)
Within the development of the research monograph, it is possible to define the potential and economic importance that Guadua Angustifolia has in our country for many years, being this an elementary plant for the development and livelihood of many families. The departments can be analyzed as the largest planted area and production and export capacity as raw material and finished products, thus showing some of the main companies in charge of carrying out the silvicultural exploitation process as an economic activity that contributes significantly to the economy of the region. Country. It goes so far as to show many of the qualities and benefits of this plant that has been losing its recognition and commercial value in the market, with the arrival and use of products that have replaced it, such as in the field of construction, thus seeking encourage its proper use and thus seek to strengthen its economy internationally.